Patient profile for biomarkerbased Alzheimer’s disease diagnosis in clinical practice - Yu. A. Shpilyukova; K. V. Nevzorova; E. Yu. Fedotova; S. N. Illarioshkin (Russian neurological journal, 2026)
Modern criteria for Alzheimer’s disease (AD) suppose a clinical-biological nature of the disease. The increasingly widespread adoption of biomarker-based diagnostics for AD necessitates a clearer clinical profile of patients, particularly given a range of complex clinical, organizational and financial-economic issues. Aim . To present a profile of the patient recommended for referral for biomarker-based diagnosis of AD, in accordance with international guidelines and the authors’ own experience with biomarker-based diagnosis in real-world clinical practice. Material and methods . We analyzed the results of the RCNN Cognitive Health Center’s operations over one calendar year, specifically the total number of patients and the distribution of disease etiologies. During the same period, we analyzed a local database of patients referred for AD biomarker diagnostics in CSF (Aβ1-42 and p-tau181) using Elecsys assays on the Cobas e 411 platform. Results . A total of 598 patients attended the initial consultation: MCI NDD 25% (n = 149), SCD 13% (n = 78), mixed CI 10% (n = 62), uNDD 10% (n = 58), vCI 9% (n = 54), LBD 8% (n = 50), AD 8% (n = 48), other causes of cognitive impairment 8% (n = 46), FTD 5% (n = 29), 4R-tauopathies 4% (n = 23), and the at-risk group — 0.002% (n = 1). AD biomarker analysis was performed on 93 patients (16%), most frequently in the MCI NDD group (39%). Conclusion . Our real-world clinical practice aligns with the recommendations of the Alzheimer’s Association international working group, prioritizing the phenotypic profiling of patients. The article presents a potential algorithm for selecting patients for referral to biomarker-based diagnosis of Alzheimer’s disease. Mild cognitive impairment with a neurodegenerative nature is the most typical clinical profile for referring a patient for the assessment of biomarkers associated with the AD pathological process.